2011
DOI: 10.1002/cbdv.201100053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Differences in the Aroma Composition of Free‐Run and Pressed Neutral Grape Juices Obtained from Emir (Vitis vinifera L.)

Abstract: In this study, the differences in the aroma compounds released after the free-run and pressed juices of cv. Emir grape (Vitis vinifera L.) were evaluated. Aroma compounds were obtained by liquid-liquid extraction with CH(2) Cl(2) , and then analyzed by gas chromatography (GC) and gas chromatography/mass spectrometry (GC/MS). According to the results, pressing uniformly increased the levels of the aromatic constituents, but this treatment lowered the grape juice quality for winemaking by increasing the total ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…2‐Phenyl ethanol has the second highest concentration among alcohols which normally provides flowery notes to red wines . Presence of this volatile alcohol in wines depends on the yeast type used in the fermentation, must composition, and fermentation temperatures . Another important volatile compound found in this group was hexanol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2‐Phenyl ethanol has the second highest concentration among alcohols which normally provides flowery notes to red wines . Presence of this volatile alcohol in wines depends on the yeast type used in the fermentation, must composition, and fermentation temperatures . Another important volatile compound found in this group was hexanol.…”
Section: Resultsmentioning
confidence: 99%
“…Pavez et al (2016) focused on the volatile thiols in Carmenere red wines, while Pons et al (2016) investigated the existence of new aroma compounds in specific odoriferous zones in red wine using the GC‐O technique. Although much research was conducted to observe the effect of the pomace pressing application on grape juice and wine volatiles, there is no published research that identifies and quantifies the aroma‐active compounds of wines obtained from free‐run juice and pressed pomace.…”
Section: Introductionmentioning
confidence: 99%
“…Pressing during wine fermentation process can increase the extraction of secondary metabolites present in fruits [14]. However, the high level of these secondary metabolites in juice can produce a green-herbaceous aroma in wine, reducing its overall pleasant flavor [10]. Bound volatiles in fruits cannot contribute to the overall aroma of wine due to their odorless properties.…”
Section: Resultsmentioning
confidence: 99%
“…For example, pressing treatment is a physical approach to disintegrate the structure of fruit cells, enhancing the release of aromatic compounds and volatile precursors in juice. It has been reported that the pressed juice contained higher levels of C 6 alcohols compared to the free-run juice [10]. Besides, odorless volatile precursors exist in fruit with a large amount [9].…”
Section: Introductionmentioning
confidence: 99%
“…The bound linalool concentration was three-fold higher than its odor threshold (6 lg/kg) (Fabre et al 2004). Linalool was distinguished by a floral-woody, lilac, lavender odor (Selli et al 2011). (E)-linalool oxide, (Z)-linalool oxide, linalool, a-terpineol, b-citronellol, nerol and geraniol were also reported in the glycosidic fraction of tomato cultivars (Marlatt et al 1992;Ortiz-Serrano and Gil 2007).…”
Section: Composition Of Bound Aroma Compounds In the Alida And Merve Cultivarsmentioning
confidence: 92%